Clinical Characteristics of Cataract Patients and Outcome of Cataract Surgery in Tertiary Care Hospital in Central Nepal - Shrestha, A.; Shrestha, P.; Shrestha, T.; Makaju Shrestha, R.; Shrestha, B.; Poudel, L.; Shrestha, J. K. (Kathmandu University Medical Journal, 2022)
Background Cataract remains the leading cause of avoidable blindness in low-income countries such as Nepal. Despite the availability of surgical interventions for cataract in leading institutions, still a large number of patients from remote areas delay or have difficulty in getting treatment, present late or with complications.Objective To determine the clinical characteristics and visual outcome of patients undergoing cataract surgery in Tertiary Care Hospital in Central Nepal.Method We retrospectively reviewed the medical records of 138 patients who underwent cataract surgery at a tertiary care hospital from January 2018 to September 2022. R version 4.0.3 was used for the data analysis. Categorical variables are presented as frequency (percentages) and the numerical ones are presented as mean (standard deviation).Result During follow-up visits between one to three weeks, 91.9% out of 135 patients had normal/near normal presenting visual acuity and with best correction it was 96.9% out of 131 patients. About 1.6% out of 124 operated eyes still had moderate visual impairment after best correction when they visited for follow-up at 12 weeks.Conclusion The study findings underline the ongoing gap in increasing access to cataract treatment, given the large proportion of individuals who still presented extremely late.